IMMUNOMODULATORY ACTIVITY OF THE LACTOBACILLUS DELBRUECKII SUBSP. BULGARICUS LB 86 ENZYME LYSATE - L. Lаzarenko; L. Orіabinska; T. Bohdan (Harčova Nauka ì Tehnologìâ)
The aim of the study was to immunomodulatory activity of the enzyme lysate of probiotic culture Lactobacillus delbrueckii subsp. bulgaricus LB86 for the development of a functionally active substance based on it with a deliberate action forapplication in cosmetology and medicine. In vitro and in vivo experiments, using an experimental model of intact BALB/c mice, investigated the effect of enzyme lysate on the functional activity of animal peritoneal exudate macrophages and the production of immunoregulatory cytokines, using conventional research methods. The enzyme lysate of L. delbrueckii subsp. bulgaricus LB86 showed immunomodulatory activity aimed at altering the activity of macrophages, as well as the production of pro- and anti-inflammatory cytokines, which are involved in balancing the immune response of the Th1- and Th2- type. Under the action of this enzyme lysate in vitro, the indicator of phagocytosis (PhI) of the peritoneal cavity macrophages of intact BALB/c mice was enhanced and after its intragastric administration to these mice, the increase of the parameters of spontaneous and stimulated NBT test of macrophages was observed and increase (on the 6th day after its introduction) in the levels of IL-12 and IFN-γ in the blood serum of mice treated with this enzyme lysate was noted against the background of an increase in the ratio of INF-γ/IL-4, which also indicated its potential ability to activate the cellular immune response. It has been established that the enzyme lysate of L. delbrueckii subsp. bulgaricus LB86 after intragastric administration to intact mice does not directly participate in modulation of intestinal microbiota and throughout the entire observation period in the intestinal contents the number of lacto- and bifidobacteria in the intestinal contents was maintained at the level of control indicators. The number of aerobic and optional anaerobic bacteria, including staphylococci, streptococci, colimorphic bacteria and microscopic fungi also did not change. Obtained data of immunomodulatory activity of the enzyme lysate of L. delbrueckii subsp. bulgaricus LB86 may indicate the potential prospects for its practical use in therapeutic and prophylactic drugs.